Media of Autonomy: Community Radios of Dakar - Dorelli, Jeanne (eTopia, 2010)
From September to December 2009 I conducted interviews with different actors in the field ofcommunity radio in Dakar, Senegal. These actors included practitioners or journalists, technicians and directors, consultants, trainers and project managers in NGOs specialized in media development, and civil servants from major governmental regulations institutions. Although the research literature on radio for development tends to focus on rural radio stations, I chose to focus on stations in Dakar because their urban location and physical proximity to international actors confer on them a front-line role, exacerbating the forces affecting their activity. The region of Dakar, the capital of Senegal, accounts for approximately 20 percent of the country’s population. It kept its place as the regional (West African) capital from the colonial era, housing many transnational organizations, NGOs, and cooperation agencies’ main quarters/offices and concentrating most of the country’s economic activity (United Nations 2007). Through this research I discovered that the strong presence of international developmentactors poses a significant difference between the workings of community radio in Dakar versusthe North American context.